Prevalence of Hydatid Disease Among Slaughtered Animals in Slemani Province/ Kurdistan-Iraq. - Mero, Wijdan M.S.; Jubrael, Jaladet M.S.; Hama, Abdullah A. (Science Journal of University of Zakho, 2018)
Hydatid cyst (HC) is one of the common silent zoonotic disease worldwide distributions, with medical importance and economical effect. The present study was conducted from January 2011 to March, 2012 to determine the prevalence rate of hydatid disease among slaughtered livestock including sheep, goats and cattle in Slemani province. A total of 7698 slaughtered animals were examined from different abattoirs for hydatid cyst during post mortem inspection including 6550 sheep, 348 goats and 800 cattle. The study showed that the prevalence rates among slaughtered animals were 12.7% in sheep, 4.8% in goats and 4.3% in cattle. The fertility rate of HCs was higher in sheep than that of goats and cattle furthermore, the rate of the fertility was higher in liver cysts than in lung cysts in all studied intermediate hosts.